Islamic Legal Perspective on IVF Program to Maintain Household Harmony - Defyta Nadhila Nurlaili; Sachrawi Hidayat; Moh. Muhibbin; Dzulfikar Rodhafi; Ibnu Atho’ilah (Seutia Hukamaa Cendekia, 2026)
This study examines the Islamic legal perspective on the In Vitro Fertilization (IVF) program as a means of maintaining household harmony. Infertility constitutes a significant challenge for many married couples, often generating emotional distress, social stigma, marital conflict, and, in some cases, the dissolution of marriage. Using normative juridical research and a library-based methodology, this article systematically reviews primary Islamic legal sources—the Qur'an, Hadith, classical and contemporary fiqh texts—as well as the fatwas of major Indonesian and international Islamic jurisprudential bodies. The study finds that IVF is permissible (mubah) under Islamic law when the sperm and ovum belong exclusively to a lawfully married couple, and the embryo is implanted in the wife's own uterus. Conversely, IVF conducted using donor sperm, donor eggs, or a surrogate womb is categorically prohibited (haram) because it leads to the mixing of lineage (ikhtilat al-nasab), resembles adultery in its legal consequence, and violates the overarching objectives of Islamic law (Maqasid al-Shari'ah), particularly the protection of lineage (hifz al-nasl). The article further argues that permissible IVF contributes positively to household harmony by fulfilling the Islamic ideal of a complete sakinah, mawaddah wa rahmah family, while prohibited forms introduce irreversible legal, ethical, and social complications that undermine marital stability. This research adds to the scholarly discourse by integrating contemporary medical realities with classical fiqh analysis and the concept of Maslahah Mursalah.